Acute and sub-chronic (28-day) oral toxicity profiles of newly synthesized prebiotic butyl-fructooligosaccharide in ICR mouse and Wistar rat models - Kang, Sini (Toxicol Res (Camb), 2020)
B-FOS (butyl-fructooligosaccharide) is a newly synthesized prebiotic molecule, formed by the combination of FOS and butyrate by ester bonds. B-FOS has been reported to have the potential prebiotic effect of promoting intestinal flora diversity and enhancing butyrate production. The aim of this study was to investigate the potential acute and sub-chronic toxicity of B-FOS in Institute of Cancer Research (ICR) mice and Wistar rats to verify its biosafety. ICR mice were administered a single oral gavage of B-FOS at doses of 0, 500, 1000, and 2000 mg/kg body weight and observed for signs of acute toxicity for 14 days. Sub-chronic toxicity was evaluated by repeated oral administration of B-FOS at 2000 mg/kg for 28 days, in accordance with Organization for Economic Co-operation and Development (OECD) protocol test numbers 420 and 407. No mortality or abnormal clinical signs were observed during the experimental periods after B-FOS administration. Furthermore, no significant changes in body weight, organ weight, serum biochemical parameters, or tissue histology were observed after animal sacrifice. These in vivo results indicate that B-FOS does not exert any acute or sub-chronic toxicity at a dose of 2000 mg/kg, and this novel molecule can be regarded as a safe prebiotic substance for use in the food and nutraceutical industries.